Kinematics model of snake robot considering snake scale - Khan, Md. Raisuddin; Watanabe, M.; Shafie, Amir Akramin (Science Publications, 2010)
Problem statement: In snake robot research, one of the most efficient forms of locomotion is the lateral undulation. However, lateral undulation, also known as serpentine locomotion, is illsuited for narrow spaces, as the body of the snake must assume a certain amount of curvature to propel forward. Approach: To overcome the inability to adapt to narrow spaces, a novel type of a gait was introduced in this study. Scales, often overlooked in snake locomotion research, play an important role in snake movement by increasing backward and lateral friction while minimizing it in forward direction. In this study a new kinematic structure of a snake robot was proposed that uses scales underneath the alternate links. Mathematical model of the structure for kinematics analysis was also presented. Results: Kinematics analysis of the proposed snake model showed that snake motion was possible with minimum of two actuators. However, higher numbers of actuators help distributed the driving load and provided a redundant structure for managing accidental failure of any link. Lateral displacement of the links was found to be less than the width of its body. Conclusion: Thus this structure as well as the mathematical model was expected to help built snake robots for narrow space applications like pipe inspection, disaster scenario mapping.